2015
DOI: 10.1016/j.jretai.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of and Barriers to Organic Purchase Behavior

Abstract: Using a cost-benefit approach, this study is the first to jointly investigate supply-side factors and consumer characteristics that drive or hinder organic purchases. With scanner data that track actual purchase behavior in 28 product categories, the authors find that organic products are less popular in vice categories and categories with high promotional intensity and more popular in fresh versus processed categories. Biospheric values that reflect a person's concern for the environment and animal welfare in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
240
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(259 citation statements)
references
References 51 publications
14
240
4
1
Order By: Relevance
“…Organic food has developed impressively, from a neglected niche market to the food market mainstream [1]. More and more researchers and practitioners are attracted and involved.…”
Section: Introductionmentioning
confidence: 99%
“…Organic food has developed impressively, from a neglected niche market to the food market mainstream [1]. More and more researchers and practitioners are attracted and involved.…”
Section: Introductionmentioning
confidence: 99%
“…During the previous decade, the global organic food market developed very quickly from a niche market to a broad market segment (Doorn, Verhoef, 2015). The demand for organic food is growing at an increased rate, which has led to global sales of organic food and drink reaching 80 billion US dollars in 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Smith and Paladino observed that the subjective norm, defined as the perceived social pressure to engage (or not engage) in a behavior (according to Ajzen's Theory of Planned Behaviour [46]), and familiarity also influenced Australian consumers' intention to purchase [47]. There are many additional variables that have been discussed in relation to perception and consumption motivations or hindering factors, such as price, availability, and others [45,[47][48][49][50][51][52][53][54][55][56][57][58], but they are not the focus of the present analysis.…”
Section: Introductionmentioning
confidence: 99%